PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL PADA SIKAP TERHADAP PERUBAHAN (Fokus Ekonomi, 2008)
The purpose of this study is to investigate the role of various dimensions of organizational commitment and job satisfaction in predicting various attitudes toward organizational change. The study uses a sample of 83 person, consists of  employees and lectures in Economic Faculty of Unsoed University. The response rate is 55,3 percent. Hierarchical regression analysis results showed three major findings for this research: First, job satisfaction directly and positively influences affective commitment and  various dimension of attitudes toward organizational change. Second, various dimensions of organizational commitment directly, both positively and negatively,  influences cognitive and behavioral tendency dimensions of attitudes toward organizational change. Third, affective and continuance commitment mediates the influences of job satisfaction on both cognitive and behavioral tendency dimensions of attitude toward organizational change. Implications, limitation, and recommendations for future research are discussed. Key words: job satisfaction, commitment, change